Association between Body Mass Index and Menstrual Disorders in Adolescent Girls: A Cross-Sectional Study - Hemasa Gul, Huma Gul, Fatima Rehman, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Menstrual disorders are common among adolescent girls and may significantly affect physical, psychological, and social well-being. Body Mass Index (BMI) has been identified as a potential modifiable risk factor influencing menstrual patterns; however, evidence among adolescents remains inconsistent. This study aimed to assess the prevalence of menstrual disorders and examine their association with BMI in adolescent girls. Study Design: A Cross-Sectional study. Place and Duration of the Study: The study was conducted at the Department of Obstetrics and Gynecology, Mardan Medical Complex, Mardan, over a period of six months, from January 2022 to June 2022. Materials and Methods: Data were collected from 220 adolescent girls aged 10–19 years. Data were collected using a structured questionnaire covering sociodemographic characteristics, menstrual history, lifestyle factors, and family history. Height and weight were measured to calculate BMI, which was categorized as underweight, normal, overweight, and obese. Menstrual disorders included irregular cycles, abnormal cycle length, menorrhagia, dysmenorrhea, and premenstrual syndrome (PMS). Statistical analysis was performed using chi-square tests and multivariable logistic regression. Adjusted odds ratios (AORs) with 95% confidence intervals (CIs) were calculated, and p < 0.05 was considered statistically significant. Results: The mean age of participants was 15.4 ± 2.1 years, and the mean BMI was 22.8 ± 4.1 kg/m². Overall, 50% of participants reported at least one menstrual disorder. Irregular cycles were observed in 38.6%, dysmenorrhea in 72.7% (moderate–severe: 39.1%), and menorrhagia in 20.5% of participants. Overweight (AOR = 2.15; 95% CI: 1.14–4.05; p = 0.018) and obese adolescents (AOR = 2.94; 95% CI: 1.18–7.32; p = 0.021) had significantly higher odds of menstrual disorders compared to those with normal BMI. Low physical activity (AOR = 1.92; p = 0.024) and positive family history (AOR = 2.36; p = 0.006) were also significant predictors. Conclusion: Menstrual disorders are highly prevalent among adolescent girls and are significantly associated with higher BMI. Overweight and obesity increase the likelihood of menstrual irregularities and dysmenorrhea. Early screening, lifestyle modification, and weight management strategies may help reduce menstrual health problems in this population. Keywords: Menstrual disorders, Body Mass Index, Adolescents, Dysmenorrhea, Menstrual irregularity, Cross-sectional study.